Secondary School Students' Identity and Citizenship Perceptions - Kasrasu Avcı, Emine (Bilge Akademi, 2020)
The aim of the research is to determine the secondary school students' perceptions of identity and citizenship concepts. The research is designed in a qualitative model. The study group consists of 30 5th, 6th and 7th grade students at a public secondary school in the province of Kastamonu. In the research, 5th, 6th and 7th graders were asked to paint on identity and citizenship concepts and to indicate what they want to tell with the pictures they drew. In the research, the pictures and views of the students were taken through content analysis. Secondary school students drew the picture of identity card for identity concept and pictures of “identity card” and “social values” related to citizenship concept. With the pictures they drew, the students stated that identity is “a document containing personal information” and citizenship means “adopting social values” and “awareness of the individual rights, duty and responsibilities”.
Keywords: 4. Education